IMPLEMENTASI DIGITAL TQM PADA MADRASAH IBTIDAIYAH SE-KECAMATAN WEDUNG: DETERMINASI BUDAYA ORGANISASI, HAMBATAN MANAJERIAL, DAN AKSELERASI PRESTASI BELAJAR - Umi Maghdhuroh; Sutama Sutama; Achmad Fathoni (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of Digital Total Quality Management (Digital TQM) in Islamic Elementary Schools (Madrasah Ibtidaiyah) in Wedung District, Demak Regency, with a focus on organizational culture, managerial barriers, and their implications for student achievement. The research is motivated by the increasing demands for digital transformation in educational quality management that have not been accompanied by adequate organizational readiness and managerial capacity. The study used a qualitative approach with a multi-site case study design. Data were collected through semi-structured interviews, participant observation, and documentation studies. Informants consisted of madrasah principals, teachers, madrasah operators, and supervisors selected through purposive and snowball sampling techniques. Data analysis used the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that commitment to quality, transformational leadership, collaboration, and openness to innovation are the main factors supporting the implementation of Digital TQM. Conversely, limited digital competency, technological infrastructure, budget, and resistance to change are the main obstacles. The implementation of Digital TQM encourages the digitization of administration, data-driven decision-making, and the strengthening of more systematic quality evaluation. Furthermore, Digital TQM contributes to improved learning quality, student engagement, and academic achievement.